Consumption of Functional Food by Cardiovascular Disease and Its Role in Disease Management - Yanie, Taw; Shaida, Bushra (Journal for Research in Applied Sciences and Biotechnology, 2022)
Consumption of functional food by cardiovascular disease patient plays a very important role in their management. Due to the increase globalization and changes in lifestyle, many adult populations are at high risk of hypertension and have contributed to high mortality and morbidity and related CVD risk. The purpose of this study is to assess the nutritional status of CVD patient and their intake of functional food. Many studies regarding functional food have confirmed that nutrition has great impact for prevention of chronic disease as most of them are consumed in daily life. The tool used for this study is questionnaire-based form which is physically ask by visiting the hospital. The expected outcome is we would get to know about if a patient is including any functional food in the diet and also, we would be able to know about the role of its in disease management. From this study, it has been found that many CVD patients are not aware of the importance of functional foods.